Raising strategic awareness of Thai EFL students of science and technology disciplines through metacognitive strategy training - Songyut Akkakoson, (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2012)
Previous studies have established that good readers’ metacognitive awareness of strategic reading processes, repertoires of reading strategies and effective strategy use can be teachable to poor readers, which results in reading achievement gains. This instructional study reports 82 Thai EFL students of science and technology who were trained in the co-ordinated use of multiple strategies to develop awareness of how to be strategic when reading English general texts. This strategy training it was hoped would increase student awareness about reading strategies taught in class (declarative knowledge), how to use these strategies (procedural knowledge) and when and why to use them (situational knowledge), which in turn may result in increased reading achievement. Results suggested that higher-level reading proficiency learners (a) were more aware of procedural knowledge of how they as readers should employ the reading strategies taught in the lessons, whereas (b) low-level reading proficiency learners made a better improvement on a standardised English reading comprehension test. The findings indicated that the metacognitive strategy training employed result in greater student awareness of both lesson content and the need to be strategic and monitor comprehension, which leads to the students’ more conscious use of strategic reasoning and higher achievement growth.